A Study on the Ability of First Grade Students in Communicating Language at SDN 005 Bukit Ranah, Kampar - Febrialismanto, Febrialismanto; Nur, Hidayatun (Proceedings of the UR International Conference on Educational Sciences, 2018)
Beforestudying at elementary school, children should study in early education. One of the childrens early education was conducted at PAUD institutions. Here, thestudents give stimulants to grow and improve properly. One of them is the ability to communicate language. In communicating language, the children are easy to communicate with others in their environment. From the research findingsthat conducted at 005 Public Elementary School Bukit Ranah, Kampar, it is known that three indicators are communicating orally, having vocabulary, and knowing symbols inreading, writing and counting, For further information, they also continuethe stories that have been played and demonstratetheir understanding ofthe story.